IMPACT OF SOCIO-ECONOMIC STATUS ON SELF CONCEPT OF THE ADOLESCENT LEARNERS - Pradhan, Mammon; Dash, Lopamudra (ShodhKosh: Journal of Visual and Performing Arts, 2025)
In the present research paper, the impact of socio-economic status (SES) on self-concept of the adolescent learners of class XI in Khairput Block of Malkangiri District, Odisha was studied. The “Updated Kuppuswamy Socioeconomic Status Classification Scale for the Indian Population 2023” and “Standardized tool of Self-Concept Questionnaire (SCQ) developed by Dr. R. K. Saraswat” were used to collect sample data. The finding of this study highlights that the socio-economic status of the learners put significant impact on the self-concept of the adolescent learners. Higher is the socio-economic status, higher is the self-concept level of the adolescent learner and vice-versa. Again, it has been found that there is no significant difference between the self-concept level of the adolescent boys and girls. This study has been conducted in a tribal district of Odisha where a wide verity of people with different culture and socio-economic status can be found. Hence, the findings of this study may help the teachers to make appropriate strategies and conduct various activities to develop self-concept of the adolescent learners having different socio-economic status.